Visual and brainstem auditory evoked potentials in infants with severe vitamin B12 deficiency - (:unkn) unknown (My University, 2015)
0

Background/aim: Vitamin B12 plays an important role in the development of mental, motor, cognitive, and social functions via its role in DNA synthesis and nerve myelination. Its deficiency in infants might cause neuromotor retardation as well as megaloblastic anemia. The objective of this study was to investigate the effects of infantile vitamin B12 deficiency on evoked brain potentials and determine whether improvement could be obtained with vitamin B12 replacement at appropriate dosages. Materials and methods: Thirty patients with vitamin B12 deficiency and 30 age-matched healthy controls were included in the study. Hematological parameters, visual evoked potentials, and brainstem auditory evoked potentials tests were performed prior to treatment, 1 week after treatment, and 3 months after treatment. Results: Visual evoked potentials (VEPs) and brainstem auditory evoked potentials (BAEPs) were found to be prolonged in 16 (53.3%) and 15 (50%) patients, respectively. Statistically significant improvements in VEP and BAEP examinations were determined 3 months after treatment. Three months after treatment, VEP and BAEP examinations returned to normal in 81.3% and 53.3% of subjects with prolonged VEPs and BAEPs, respectively. Conclusion: These results demonstrate that vitamin B12 deficiency in infants causes significant impairment in the auditory and visual functioning tests of the brain, such as VEP and BAEP.
Keywords: Cerrahi